Ceramic binder slurry, preparation method thereof and gas sensor chip

By using ceramic binder slurry of specific component ratios as the connecting layer, the problem of layering and cracking of the ceramic layer after sintering of the traditional oxygen sensor chip is solved, and the yield and performance stability of the chip are improved.

CN119390443APending Publication Date: 2025-02-07CHINA FAW CO LTD

Patent Information

Application Number
CN202411505134.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

After sintering, traditional oxygen sensor chips are prone to cracking in the alumina insulating layer and zirconia ceramic layer, which affects the performance of the device.

Method used

A ceramic binder slurry is provided, including yttrium stabilized zirconia powder, organic solvents, binders, plasticizers, dispersants, thixotropic agents and lubricants, combined with specific proportions of these components for The zirconia substrates in the gas sensor chip are used as the connecting layer slurry to enhance the bonding force between the zirconia substrates.

Benefits of technology

It effectively reduces the chance of ceramic layer layering and cracking caused by inconsistent sintering temperature and shrinkage during co-sintering of zirconia substrate and alumina insulating layer, and improves the yield rate of gas sensor chips.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390443A_ABST
    Figure CN119390443A_ABST
Patent Text Reader

Abstract

The invention provides ceramic binder slurry, a preparation method thereof and a gas sensor chip. The ceramic binder slurry comprises the following components in percentage by mass: 65-73% of yttrium-stabilized zirconia powder, 15-21% of an organic solvent, 4-6% of a binder, 1-3% of a plasticizer, 1-2% of a dispersant, 1-2% of a thixotropic agent and 1-2% of a lubricant. The ceramic binder slurry provided by the invention can effectively enhance the binding force between zirconium oxide substrates, thereby reducing the probability of layering and cracking of a ceramic layer of a sintered gas sensor chip due to inconsistent sintering temperature and shrinkage rate in the co-sintering process of the zirconium oxide substrates and an aluminum oxide insulating layer; and the yield of the gas sensor chip is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of gas sensors, and in particular to a ceramic binder slurry and a preparation method thereof, and a gas sensor chip. Background Art

[0002] A gas sensor is a conversion device that converts the concentration of a certain gas into a corresponding electrical signal. Among them, the oxygen sensor is used to measure the oxygen content in the exhaust gas after the combustion of the automobile engine, and convert it into an electrical signal to feed back to the automobile electronic control unit (ECU). The ECU uses the optimal combustion state (air excess coefficient λ=1) as a benchmark to determine whether there is excess oxygen in this state, and controls the injection amount of the injector accordingly, minimizing additional fuel loss and converting and purifying exhaust pollutants. It is an important component for achieving automobile energy conservation and emission reduction. Among them, the chip oxygen sensor has the advantages of small size, short response time, and resistance to harsh environments, and has become the mainstream product of automotive oxygen sensors.

[0003] The chip oxygen sensor chip mainly includes the following parts: outer electrode layer, zirconium oxide substrate, inner electrode layer, reference air channel layer and heating electrode layer. By casting the ceramic slurry, a ceramic film strip can be obtained, which is then cut, punched, printed, laminated, statically pressed, hot cut and sintered to finally realize the preparation of the chip oxygen sensor. The chip oxygen sensor chip usually uses zirconium oxide as the substrate (solid electrolyte material), and prints the heating electrode layer on it to maintain the appropriate working temperature environment of the zirconium oxide substrate. Among them, the heating electrode layer structure mainly includes two upper and lower aluminum oxide insulating layers covering the middle heating electrode (usually a metal platinum electrode), and the upper and lower aluminum oxide insulating layers are used to achieve the purpose of electrical insulation between the heating electrode and other components. In the preparation process of the chip oxygen sensor chip, the co-firing of the zirconium oxide substrate and the aluminum oxide insulating layer is involved. However, after sintering, the traditional oxygen sensor chip is prone to delamination and cracking of the aluminum oxide insulating layer and the zirconium oxide substrate, which affects the performance of the device.

[0004] Therefore, the traditional technology still needs to be further improved. Summary of the invention

[0005] Based on this, the present application provides a ceramic binder slurry that can reduce delamination and cracking after co-firing of a zirconium oxide substrate and an aluminum oxide insulating layer, and correspondingly provides a method for preparing the ceramic binder slurry and a gas sensor chip.

[0006] The technical solution proposed in this application is as follows:

[0007] According to a first aspect of the present application, a ceramic binder slurry is provided, comprising the following components by mass percentage:

[0008] Yttrium stabilized zirconia powder 65%~73%, organic solvent 15%~21%, binder 4%~6%, plasticizer 1%~3%, dispersant 1%~2%, thixotropic agent 1%~2%, lubricant 1%~2%.

[0009] In any embodiment, the D50 particle size of the yttrium-stabilized zirconia powder is 0.4 μm to 0.8 μm.

[0010] In any embodiment, the organic solvent includes a kinetic solvent and a thermodynamic solvent, the kinetic solvent includes one or more of ethanol, isopropanol and terpineol, and the thermodynamic solvent includes one or more of butanone, ethyl acetate and methyl ethyl ketone.

[0011] In any embodiment, the binder includes one or more of ethyl cellulose and polyvinyl butyral.

[0012] In any embodiment, the plasticizer includes one or more of butyl benzyl phthalate, polyethylene glycol, diethyl phthalate, and dibutyl phthalate.

[0013] In any embodiment, the dispersant includes one or more of polyvinyl pyrrolidone, triethanolamine and fish oil.

[0014] In any embodiment, the thixotropic agent includes one or more of hydrogenated castor oil, polyamide wax and modified urea solution.

[0015] In any embodiment, the lubricant includes one or more of glycerol and isobutyl methacrylate.

[0016] According to the second aspect of the present application, there is provided a method for preparing the ceramic binder slurry according to the first aspect of the present application, comprising the following steps:

[0017] Mixing yttrium-stabilized zirconia powder, an organic solvent and a dispersant and ball-milling to obtain a first slurry;

[0018] The first slurry is mixed with a binder and subjected to ball milling to obtain a second slurry;

[0019] The second slurry is mixed with a plasticizer and a lubricant and subjected to ball milling to obtain a third slurry;

[0020] The third slurry is mixed with a thixotropic agent and ball-milled, and then filtered, degassed and homogenized in sequence to obtain a ceramic binder slurry.

[0021] According to a third aspect of the present application, a gas sensor chip is provided, comprising a first zirconia substrate, a heating electrode layer, a connecting layer, and a second zirconia substrate, wherein the first zirconia substrate, the heating electrode layer, and the second zirconia substrate are stacked in sequence, the heating electrode layer comprises a first aluminum oxide insulating layer, a heating electrode, and a second aluminum oxide insulating layer stacked in sequence from the first zirconia substrate to the second zirconia substrate, the connecting layer is arranged between the first zirconia substrate and the second zirconia substrate and is arranged in the same layer as the heating electrode layer, and the raw material of the connecting layer comprises the ceramic binder slurry of the first aspect of the present application.

[0022] In any embodiment, the connection layer is disposed around the outside of the heating electrode layer; and / or the thickness of the connection layer is greater than or equal to the thickness of the heating electrode layer.

[0023] Compared with the traditional technology, this application has at least the following beneficial effects:

[0024] The ceramic binder slurry of the present application includes specific contents of yttrium-stabilized zirconia powder, organic solvent, binder, plasticizer, dispersant, thixotropic agent and lubricant; by combining the above components at specific contents, when the ceramic binder slurry is used as a connecting layer slurry between the zirconia substrates in the gas sensor chip, the bonding force between the zirconia substrates can be effectively enhanced, and the probability of ceramic layer delamination and cracking in the gas sensor chip after sintering due to inconsistent shrinkage rates between the zirconia substrate and the alumina insulating layer during co-sintering can be reduced, thereby improving the yield of the gas sensor chip. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to better describe and illustrate the embodiments or examples provided by the present application, reference may be made to one or more drawings. The additional details or examples used to describe the drawings should not be considered as limiting the scope of the disclosed application, the embodiments or examples currently described, and any of the best modes of these applications currently understood. Moreover, the same reference numerals are used throughout the drawings to represent the same components. In the drawings:

[0026] Figure 1 FIG. 1 is an exploded view of a gas sensor chip in one embodiment of the present application.

[0027] Description of reference numerals:

[0028] 1. Gas sensor chip; 11. First zirconium oxide substrate; 12. Heating electrode layer; 13. Connecting layer; 14. Second zirconium oxide substrate; 15. External electrode protection layer; 16. External electrode layer; 17. Third zirconium oxide substrate; 18. Internal electrode layer; 19. Reference gas channel layer; 121. First aluminum oxide insulating layer; 122. Heating electrode; 123. Second aluminum oxide insulating layer. DETAILED DESCRIPTION

[0029] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail. In the following description, many specific details are set forth to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application, so the present application is not limited by the specific embodiments disclosed below.

[0030] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present application. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the present application, etc. can be purchased from the market or can be prepared by existing methods.

[0031] Gas oxygen sensor chips usually use zirconium oxide as a substrate (solid electrolyte material) and print a heating electrode on it. Aluminum oxide needs to be set as an insulating layer between the zirconium oxide substrate and the heating electrode to avoid direct electrical contact between the zirconium oxide substrate and the heating electrode. In the preparation process of the above-mentioned gas sensor chip, co-firing of zirconium oxide and aluminum oxide is involved. However, traditional gas oxygen sensor chips are prone to delamination and cracking of the aluminum oxide insulating layer and the zirconium oxide ceramic layer after sintering, which affects the performance of the device.

[0032] Some embodiments of the present application provide a ceramic binder slurry, which includes the following components by mass percentage: 65%~73% yttrium stabilized zirconia (YSZ) powder, 15%~21% organic solvent, 4%~6% binder, 1%~3% plasticizer, 1%~2% dispersant, 1%~2% thixotropic agent and 1%~2% lubricant.

[0033] Traditional gas sensor chips have many problems during the sintering process, mainly the following aspects: (1) The sintering temperature of the zirconia substrate and the alumina insulating layer is inconsistent: the sintering temperature of zirconia is lower than that of alumina, which leads to the delamination of the alumina insulating layer and the zirconia substrate during the co-sintering process; (2) The sintering shrinkage rate of zirconia and alumina is inconsistent: the thermal shrinkage rates of zirconia and alumina are different, which leads to the ceramic layer cracking during the stacking sintering process.

[0034] In order to achieve the co-sintering of zirconium oxide and aluminum oxide, researchers often use methods to modify the material of the aluminum oxide layer, such as adding sintering aids to the aluminum oxide slurry to reduce its sintering temperature, or doping zirconium oxide in the aluminum oxide slurry to improve the adhesion between the aluminum oxide insulating layer and the zirconium oxide substrate. However, the above methods will sacrifice the insulation and other properties of the aluminum oxide insulating layer material. In addition, the probability of cracking of the aluminum oxide insulating layer after sintering is still very high. Therefore, it is necessary to increase the bonding strength of the two layers of zirconium oxide substrate above and below the aluminum oxide insulating layer, so as to ensure the insulation performance of aluminum oxide while making the chip structure after co-firing tight and complete, without stratification and cracking, so that the gas sensor chip has better stability.

[0035] The ceramic binder slurry mentioned above in the present application includes a specific content of yttrium-stabilized zirconia powder, an organic solvent, a binder, a plasticizer, a dispersant, a thixotropic agent and a lubricant. Among them, the yttrium-stabilized zirconia powder has high hardness, high strength and good wear resistance, can maintain structural stability under high temperature environment, does not undergo phase change or decomposition, and can make the ceramic binder slurry have good bonding with the zirconia substrate. The organic solvent can dissolve organic components such as binders and plasticizers, so that they are evenly dispersed in the slurry, and also help to disperse the yttrium-stabilized zirconia powder and prevent particle agglomeration; and, by adjusting the amount of organic solvent, the viscosity of the slurry can be controlled. The binder can bond the yttrium-stabilized zirconia powder particles together. It acts as a "glue" in the slurry to ensure that the powder particles will not loosen during processing, and can improve the fluidity and plasticity of the slurry. Plasticizers can increase the flexibility and elasticity of the coating, allowing it to deform to a certain extent when subjected to external forces without being easily broken; at the same time, plasticizers can also improve the fluidity and plasticity of the slurry. Dispersants can be adsorbed on the surface of yttrium-stabilized zirconia powder particles to form a protective film to prevent the particles from agglomerating with each other, which helps to improve the stability and uniformity of the slurry and ensure the consistency of coating performance. Thixotropic agents can make the slurry have a higher viscosity in a static state to prevent particle sedimentation and stratification; when subjected to external forces, the viscosity decreases and the fluidity increases, making the slurry easier to operate and control during processing. Lubricants can form a lubricating film between yttrium-stabilized zirconia powder particles and between particles and processing equipment to reduce friction and wear; at the same time, they can also reduce the viscosity of the slurry and improve the fluidity of the slurry.

[0036] By combining the above components at specific contents, the ceramic binder slurry has good adhesion and bonding properties when used as a connecting layer slurry between zirconia substrates, and can effectively enhance the bonding force between the zirconia substrates, reduce the probability of ceramic layer delamination and cracking in the sintered gas sensor chip due to inconsistent sintering temperature and shrinkage rate during the co-sintering process of the zirconia substrate and the alumina insulating layer, and improve the yield of the gas sensor chip.

[0037] It can be understood that the mass percentage of yttrium-stabilized zirconia powder in the above-mentioned ceramic binder slurry can be 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73% and any value within the range formed by any two of the above values; the mass percentage of organic solvent can be 15%, 16%, 17%, 18%, 19%, 20%, 21% and any value within the range formed by any two of the above values; the mass percentage of binder can be 4%, 4.5%, 5%, 5.5%, 6% and any value within the range formed by any two of the above values; the mass percentage of plasticizer can be 15%, 16%, 17%, 18%, 19%, 20%, 21% and any value within the range formed by any two of the above values The mass percentage may be 1%, 1.5%, 2%, 2.5%, 3% and any value within the range formed by any two of the above values; the mass percentage of the dispersant may be 1%, 1.2%, 1.5%, 1.8%, 2% and any value within the range formed by any two of the above values; the mass percentage of the thixotropic agent may be 1%, 1.2%, 1.5%, 1.8%, 2% and any value within the range formed by any two of the above values; the mass percentage of the lubricant may be 1%, 1.2%, 1.5%, 1.8%, 2% and any value within the range formed by any two of the above values.

[0038] In some embodiments, the D50 particle size of the yttrium-stabilized zirconia powder is 0.4 μm to 0.8 μm. Controlling the particle size of the yttrium-stabilized zirconia powder in the ceramic binder slurry within the above range is conducive to good contact between the yttrium-stabilized zirconia powder and other components of the binder slurry, improving the bonding strength of the coating, and is conducive to forming a uniform slurry, improving the stability and fluidity of the slurry.

[0039] In some embodiments, the organic solvent includes a kinetic solvent and a thermodynamic solvent; the kinetic solvent includes one or more of ethanol, isopropanol and terpineol; the thermodynamic solvent includes one or more of butanone, ethyl acetate and methyl ethyl ketone. Among them, the kinetic solvent mainly affects the rate of the reaction, and can accelerate or slow down the chemical reaction by changing the solvation state of the reactants, affecting the diffusion rate of molecules and participating in the formation of transition states; the thermodynamic solvent mainly affects the equilibrium of the reaction, and can affect the direction and limit of the reaction by changing thermodynamic parameters such as the enthalpy change, entropy change and free energy change of the reaction.

[0040] In some embodiments, the binder includes one or more of ethyl cellulose and polyvinyl butyral. The use of the above specific types of binders is more conducive to improving the bonding strength between the zirconia substrates and reducing the probability of ceramic layer delamination and cracking after the zirconia substrate and the alumina insulating layer are co-sintered.

[0041] Among them, ethyl cellulose is a non-ionic cellulose ether that is insoluble in water but soluble in organic solvents, and has good thermal stability, chemical stability and high mechanical strength; polyvinyl butyral has good cold resistance and impact resistance, and as a binder it can provide good bonding properties and improve the adhesion and durability of the coating.

[0042] In some embodiments, the plasticizer includes one or more of butyl benzyl phthalate, polyethylene glycol, diethyl phthalate and dibutyl phthalate. The use of the above-mentioned types of plasticizers is beneficial to increase the flexibility and elasticity of the coating, and is also beneficial to improve the fluidity and plasticity of the slurry.

[0043] In some embodiments, the dispersant includes one or more of polyvinyl pyrrolidone, triethanolamine and fish oil. The use of the above-mentioned dispersants is more conducive to avoiding the mutual agglomeration of yttrium-stabilized zirconia powder particles, and helps to improve the stability and uniformity of the slurry and the consistency of coating performance.

[0044] Among them, polyvinyl pyrrolidone is miscible with a variety of organic solvents and can form a stable solution within a wide concentration range. Triethanolamine is miscible with a variety of organic solvents and has a certain surface activity. It can reduce the surface tension of the liquid and help improve the adsorption capacity of the dispersant on the particle surface, thereby better achieving the dispersion effect. Fish oil is a natural substance extracted from fish, with good biocompatibility and environmental friendliness. The fatty acids in fish oil can reduce the surface tension of the liquid, making the particles easier to disperse in the liquid, helping to improve the stability of the slurry and prevent particle agglomeration. Fish oil molecules can also adsorb on the surface of the particles to form a steric hindrance layer to prevent direct contact between particles, thereby maintaining the dispersed state of the particles.

[0045] In some embodiments, the thixotropic agent includes one or more of hydrogenated castor oil, polyamide wax and modified urea solution. The use of the above-mentioned thixotropic agent is more conducive to avoiding the sedimentation and stratification of the yttrium-stabilized zirconia powder particles, and making the ceramic binder slurry have suitable viscosity and good fluidity.

[0046] Hydrogenated castor oil, polyamide wax and modified urea solution all have excellent thixotropy, good thermal stability, and good compatibility with a variety of systems. They can form a three-dimensional network structure in a static state, which makes the system have a high viscosity and effectively prevents the sedimentation of particles; when subjected to shear force, the network structure is destroyed, the viscosity is reduced, the fluidity of the system is increased, and it is easy to construct. Among them, the modified urea solution refers to the solution formed by modifying the urea molecule by chemical structure modification, blending modification or physical treatment modification.

[0047] In some embodiments, the lubricant includes one or more of glycerol and isobutyl methacrylate. The use of the above-mentioned lubricants is more conducive to reducing friction and wear, reducing the viscosity of the slurry, and improving the fluidity of the slurry.

[0048] Some embodiments of the present application provide a method for preparing the ceramic binder slurry mentioned above in the present application, and the preparation method comprises the following steps: first, yttrium-stabilized zirconia powder, an organic solvent and a dispersant are mixed and ball-milled to obtain a first slurry; then the first slurry is mixed and ball-milled with a binder to obtain a second slurry; then the second slurry is mixed and ball-milled with a plasticizer and a lubricant to obtain a third slurry; the third slurry is mixed and ball-milled with a thixotropic agent, and then filtered, degassed and homogenized in sequence to obtain a ceramic binder slurry.

[0049] In some of the embodiments, in the ball milling process of forming the first slurry, the ball milling speed is 180 rpm to 300 rpm, and the ball milling time is 16 hours; in the ball milling process of forming the second slurry, the ball milling speed is 180 rpm to 300 rpm, and the ball milling time is 12 hours; in the ball milling process of forming the third slurry, the ball milling speed is 180 rpm to 300 rpm, and the ball milling time is 12 hours; in the process of mixing the third slurry with the thixotropic agent and ball milling, the ball milling speed is 180 rpm to 300 rpm, and the ball milling time is 24 hours to 30 hours; the mixed material is filtered using a 300-mesh to 400-mesh filter.

[0050] See also Figure 1 In some embodiments of the present application, a gas sensor chip 1 is provided, which includes a first zirconium oxide substrate 11, a heating electrode layer 12, a connecting layer 13 and a second zirconium oxide substrate 14. The first zirconium oxide substrate 11, the heating electrode layer 12 and the second zirconium oxide substrate 14 are stacked in sequence; the heating electrode layer 12 includes a first aluminum oxide insulating layer 121, a heating electrode 122 and a second aluminum oxide insulating layer 123 stacked in sequence from the first zirconium oxide substrate 11 to the second zirconium oxide substrate 14; the connecting layer 13 is arranged between the first zirconium oxide substrate 11 and the second zirconium oxide substrate 14 and is arranged in the same layer as the heating electrode layer 12, and the raw material of the connecting layer 13 includes the ceramic binder slurry mentioned above in the present application.

[0051] By setting a connecting layer 13 between the first zirconia substrate 11 and the second zirconia substrate 14 of the gas sensor chip 1, and the connecting layer 13 adopts the ceramic adhesive slurry mentioned in the present application as the material, the connecting layer 13 has good adhesion and bonding properties, and can effectively enhance the bonding force between the two layers of zirconia substrates, and reduce the probability of ceramic layer delamination and cracking of the gas sensor chip 1 after sintering due to inconsistent sintering temperature and shrinkage rate during the co-sintering process of the zirconia substrate and the alumina insulating layer, thereby improving the yield of the gas sensor chip 1.

[0052] See also Figure 1 In some embodiments, the gas sensor chip 1 further includes an outer electrode protection layer 15, an outer electrode layer 16, a third zirconium oxide substrate 17, an inner electrode layer 18 and a reference gas channel layer 19. The reference gas channel layer 19 is disposed on the surface of the second zirconium oxide substrate 14 away from the heating electrode layer 12; the outer electrode layer 16 and the inner electrode layer 18 are respectively disposed on the upper and lower surfaces of the third zirconium oxide substrate 17, and the inner electrode layer 18 is close to the reference gas channel layer 19; and the outer electrode protection layer 15 is disposed on the outer electrode layer 16.

[0053] The present application will be further described below in conjunction with specific embodiments and comparative examples, but they should not be construed as limiting the scope of protection of the present application.

[0054] Slurry Example 1:

[0055] Yttrium-stabilized zirconia powder (D50 particle size: 0.6 μm) accounting for 65% of the slurry mass percentage, 21% of organic solvent (ethanol and butanone each accounting for half volume) and 2% of dispersant polyvinyl pyrrolidone were loaded into a zirconia ball mill, the ball mill speed was set to 200 rpm, and the ball mill time was set to 16 hours;

[0056] Ethyl cellulose, a binder accounting for 5% by mass of the slurry, was placed into the above-mentioned zirconium oxide ball mill, the ball mill speed was set to 200 rpm, and the ball mill time was set to 12 hours;

[0057] 3% of the plasticizer butyl benzyl phthalate and 2% of the lubricant glycerol, which account for 3% of the slurry by mass, are placed in the above-mentioned zirconium oxide ball mill, the ball mill speed is set to 200 rpm, and the ball mill time is set to 12 hours;

[0058] Add 2% by weight of thixotropic agent hydrogenated castor oil into the above-mentioned zirconium oxide ball mill, set the ball mill speed to 200 rpm, and set the ball mill time to 26 hours to obtain a slurry mixture;

[0059] The slurry mixture obtained above was filtered through a 300-mesh filter, degassed, and then treated by a homogenizer to obtain a uniform and stable ceramic binder slurry, which was recorded as slurry 1.

[0060] Slurry Example 2:

[0061] Yttrium-stabilized zirconia powder (D50 particle size: 0.6 μm) accounting for 70% of the slurry mass percentage, 16% of an organic solvent (ethanol and butanone each accounting for half of the volume) and 2% of a dispersant, polyvinyl pyrrolidone, were loaded into a zirconia ball mill, the ball mill speed was set to 200 rpm, and the ball mill time was set to 16 hours;

[0062] Ethyl cellulose, a binder accounting for 5% by mass of the slurry, was placed into the above-mentioned zirconium oxide ball mill, the ball mill speed was set to 200 rpm, and the ball mill time was set to 12 hours;

[0063] 3% of the plasticizer butyl benzyl phthalate and 2% of the lubricant glycerol, which account for 3% of the slurry by mass, are placed in the above-mentioned zirconium oxide ball mill, the ball mill speed is set to 200 rpm, and the ball mill time is set to 12 hours;

[0064] Add 2% by weight of thixotropic agent hydrogenated castor oil into the above-mentioned zirconium oxide ball mill, set the ball mill speed to 200 rpm, and set the ball mill time to 26 hours to obtain a slurry mixture;

[0065] The slurry mixture obtained above was filtered through a 300-mesh filter, degassed, and then treated by a homogenizer to obtain a uniform and stable ceramic binder slurry, which was recorded as slurry 2.

[0066] Slurry Example 3:

[0067] Yttrium-stabilized zirconia powder (D50 particle size: 0.6 μm) accounting for 73% of the slurry mass percentage, 15% of an organic solvent (ethanol and butanone each accounting for half of the volume) and 1% of a dispersant, polyvinyl pyrrolidone, were loaded into a zirconia ball mill, the ball mill speed was set to 200 rpm, and the ball mill time was set to 16 hours;

[0068] Ethyl cellulose, a binder accounting for 5% by mass of the slurry, was placed into the above-mentioned zirconium oxide ball mill, the ball mill speed was set to 200 rpm, and the ball mill time was set to 12 hours;

[0069] 2% of the plasticizer butyl benzyl phthalate and 2% of the lubricant isobutyl methacrylate, which account for 2% of the slurry by mass, are placed in the above-mentioned zirconium oxide ball mill, the ball mill speed is set to 200 rpm, and the ball mill time is set to 12 hours;

[0070] The thixotropic agent polyamide wax accounting for 2% by mass of the slurry is added into the above-mentioned zirconium oxide ball mill, the ball milling speed is set to 200 rpm, and the ball milling time is set to 26 hours to obtain a slurry mixture;

[0071] The slurry mixture obtained above was filtered through a 300-mesh filter, degassed, and then treated by a homogenizer to obtain a uniform and stable ceramic binder slurry, which was recorded as slurry 3.

[0072] Slurry Comparative Example 1:

[0073] 50% of the slurry mass percentage of yttrium-stabilized zirconia powder (D50 particle size is 0.6 μm), 38% of organic solvent (ethanol and butanone each account for half of the volume) and 1% of dispersant polyvinyl pyrrolidone are loaded into a zirconia ball mill, the ball mill speed is set to 200 rpm, and the ball mill time is set to 16 hours;

[0074] Ethyl cellulose, a binder accounting for 5% by mass of the slurry, was placed into the above-mentioned zirconium oxide ball mill, the ball mill speed was set to 200 rpm, and the ball mill time was set to 12 hours;

[0075] 2% of the plasticizer butyl benzyl phthalate and 2% of the lubricant isobutyl methacrylate, which account for 2% of the slurry by mass, are placed in the above-mentioned zirconium oxide ball mill, the ball mill speed is set to 200 rpm, and the ball mill time is set to 12 hours;

[0076] The thixotropic agent polyamide wax accounting for 2% by mass of the slurry is added into the above-mentioned zirconium oxide ball mill, the ball milling speed is set to 200 rpm, and the ball milling time is set to 26 hours to obtain a slurry mixture;

[0077] The slurry mixture obtained above was filtered through a 300-mesh filter, degassed, and then treated by a homogenizer to obtain a uniform and stable ceramic binder slurry, which was recorded as slurry 4.

[0078] Slurry Comparative Example 2:

[0079] Yttrium-stabilized zirconia powder (D50 particle size: 0.6 μm) accounting for 73% of the slurry mass percentage, 21% of organic solvent (ethanol and butanone each accounting for half volume) and 1% of dispersant polyvinyl pyrrolidone were loaded into a zirconia ball mill, the ball mill speed was set to 200 rpm, and the ball mill time was set to 16 hours;

[0080] 5% of the slurry by weight of ethyl cellulose as a binder is placed in the above-mentioned zirconium oxide ball mill, the ball milling speed is set to 200 rpm, and the ball milling time is set to 12 hours to obtain a slurry mixture;

[0081] The slurry mixture obtained above was filtered through a 300-mesh filter, degassed, and then treated by a homogenizer to obtain a uniform and stable ceramic binder slurry, which was recorded as slurry 5.

[0082] Device Example 1:

[0083] Printing an alumina insulating slurry on the first zirconia substrate, placing it in a high-temperature blast drying oven, and drying it at 60° C. to 65° C. for 10 minutes to form a first alumina insulating layer; the size of the first alumina insulating layer is smaller than the size of the first zirconia substrate, and a region for printing a connection layer is formed between the edge of the first zirconia substrate and the edge of the first alumina insulating layer;

[0084] Printing a heating electrode on the first alumina insulating layer, placing it in a high-temperature blast drying oven, and drying it at 60°C to 65°C for 10 minutes to completely insulate the heating electrode from the first zirconium oxide substrate; Printing an alumina insulating layer slurry on the heating electrode, placing it in a high-temperature blast drying oven, and drying it at 60°C to 65°C for 10 minutes to form a second alumina insulating layer, thereby forming a heating electrode layer;

[0085] The slurry 1 is printed in the area for printing the connecting layer on the first zirconia substrate, and the slurry is placed in a high-temperature forced air drying oven and dried at 60°C~65°C for 10 minutes to form a connecting layer; the thickness of the connecting layer is equal to the thickness of the heating electrode layer; the second zirconia substrate is stacked on the connecting layer and the heating electrode layer, and then a reference air channel layer is prepared on the second zirconia substrate, and a third zirconia substrate having an outer electrode layer and an inner electrode layer on the upper and lower sides respectively, with the side of the inner electrode layer being stacked on the reference air channel layer, an outer electrode protective layer is arranged on the outer electrode layer, and co-sintering is performed at 1450°C after hot pressing to obtain a gas sensor chip, and the above-mentioned gas sensor chip is used to make an oxygen sensor.

[0086] Device Example 2~Device Example 3:

[0087] Device Example 2 and Device Example 3 are substantially the same as Device Example 1, except that slurry 2 and slurry 3 are used instead of slurry 1, respectively.

[0088] Device Comparison Example 1~Device Comparison Example 2:

[0089] Device Comparative Example 1 and Device Comparative Example 2 are substantially the same as Device Example 1, except that Slurry 4 and Slurry 5 are used instead of Slurry 1, respectively.

[0090] Device comparison example 3:

[0091] Device Comparative Example 3 is substantially the same as Device Example 1, except that no connection layer is provided between the first zirconia substrate and the second zirconia substrate.

[0092] It was observed whether delamination and cracking occurred after co-firing the zirconium oxide substrate and the aluminum oxide insulating layer in the gas sensor chip prepared in the above device embodiments. The test results are shown in Table 1.

[0093] Table 1

[0094]

[0095] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0096] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.

Claims

1. A ceramic binder slurry, characterized in that: The following components are included by mass percentage: Yttrium stabilized zirconia powder 65%~73%, organic solvent 15%~21%, binder 4%~6%, plasticizer 1%~3%, dispersant 1%~2%, thixotropic agent 1%~2%, lubricant 1%~2%.

2. The ceramic binder slurry according to claim 1, characterized in that: The D50 particle size of the yttrium-stabilized zirconia powder is 0.4 μm to 0.8 μm.

3. The ceramic binder slurry according to claim 1, characterized in that: The organic solvent includes a kinetic solvent and a thermodynamic solvent. The kinetic solvent includes one or more of ethanol, isopropanol and terpineol. The thermodynamic solvent includes one or more of butanone, ethyl acetate and methyl ethyl ketone.

4. The ceramic binder slurry according to claim 1, characterized in that: The binder includes one or more of ethyl cellulose and polyvinyl butyral.

5. The ceramic binder slurry according to claim 1, characterized in that: The plasticizer includes one or more of butyl benzyl phthalate, polyethylene glycol, diethyl phthalate and dibutyl phthalate.

6. The ceramic binder slurry according to claim 1, characterized in that: The dispersant includes one or more of polyvinyl pyrrolidone, triethanolamine and fish oil.

7. The ceramic binder slurry according to any one of claims 1 to 6, characterized in that The thixotropic agent includes one or more of hydrogenated castor oil, polyamide wax and modified urea solution.

8. The ceramic binder slurry according to any one of claims 1 to 6, characterized in that: The lubricant includes one or more of glycerol and isobutyl methacrylate.

9. A method for preparing a ceramic binder slurry according to any one of claims 1 to 8, characterized in that: The following steps are involved: Mixing yttrium-stabilized zirconia powder, an organic solvent and a dispersant and ball-milling to obtain a first slurry; The first slurry is mixed with a binder and subjected to ball milling to obtain a second slurry; The second slurry is mixed with a plasticizer and a lubricant and subjected to ball milling to obtain a third slurry; The third slurry is mixed with a thixotropic agent and ball-milled, and then filtered, degassed and homogenized in sequence to obtain a ceramic binder slurry.

10. A gas sensor chip, characterized in that: It includes a first zirconia substrate, a heating electrode layer, a connecting layer and a second zirconia substrate, wherein the first zirconia substrate, the heating electrode layer and the second zirconia substrate are stacked in sequence, the heating electrode layer includes a first aluminum oxide insulating layer, a heating electrode and a second aluminum oxide insulating layer stacked in sequence from the first zirconia substrate to the second zirconia substrate, the connecting layer is arranged between the first zirconia substrate and the second zirconia substrate and is arranged in the same layer as the heating electrode layer, and the raw material of the connecting layer includes the ceramic binder slurry described in any one of claims 1 to 8.

11. The gas sensor chip according to claim 10, characterized in that: The connection layer is arranged around the outer side of the heating electrode layer; And / or, the thickness of the connecting layer is greater than or equal to the thickness of the heating electrode layer.

Citation Information

Patent Citations

  • Porous diffusion barrier material applicable to oxygen sensor chip

    CN107064270A

  • Bonding layer slurry preparation material, preparation method and gas sensor

    CN112242210A

  • Binder slurry for nitrogen-oxygen sensor as well as preparation method and application of binder slurry

    CN115746750A

  • Preparation method of ceramic binder for nitrogen-oxygen sensor

    CN118684515A

  • Automobile -used oxygen sensor chip that contains ceramic bond

    CN206671240U

Cited By

  • Zirconium oxide-based gas sensor electrode wire slurry and preparation method thereof

    CN119811745A

  • Bonding slurry for sensor and preparation method thereof

    CN120622944A

  • Polyborosilazane-based ceramic binder as well as preparation method and application thereof

    CN120795863A